Molecular and microbiological report of a hospital outbreak of NDM-1-carrying Enterobacteriaceae in Mexico - Nübel, Ulrich; Bocanegra Ibarias, Paola; Garza González, Elvira; Morfín Otero, Rayo; Barrios, Humberto; Villarreal Treviño, Licet; Rodríguez Noriega, Eduardo; Garza Ramos, Ulises; Petersen Morfin, Santiago; Silva Sánchez, Jesús (2017)
Objectives To characterize the microbiological, molecular and epidemiological data of an outbreak of carbapenem-resistant Enterobacteriaceae (CRE) in a tertiary-care hospital in Mexico. Methods From September 2014 to July 2015, all CRE clinical isolates recovered during an outbreak in the Hospital Civil "Fray Antonio Alcalde" in Jalisco, Mexico were screened for antimicrobial susceptibility, carbapenemase production, carbapenemase-encoding genes, and plasmid profiles. Horizontal transfer of imipenem resistance; and clonal diversity by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST); as well as biofilm production and the presence of 14 virulence genes were analyzed in selected isolates. Results Fifty-two carbapenem-resistant isolates corresponding to 5 species were detected, i.e., Klebsiella pneumoniae (n = 46), Enterobacter cloacae (n = 3), Escherichia coli (n = 1), Providencia rettgeri (n = 1) and Citrobacter freundii (n = 1) with carbapenemase encoding genes blaNDM-1 (n = 48), blaVIM (n = 3), blaIMP (n = 1) and blaKPC (n = 1) detected in these isolates. The blaNDM-1 gene was detected in plasmids from 130- to 170-kb in K. pneumoniae (n = 46); E. cloacae (n = 3), E. coli (n = 1) and P. rettgeri (n = 1). The transfer of plasmids harboring the blaNDM-1 gene was obtained in eight transconjugants. One plasmid restriction pattern was detected, with the blaNDM-1 identified in different restriction fragments. Predominant clone A of K. pneumoniae isolates archived 28/46 (60%) isolates and belongs to ST392. Besides, ST307, ST309, ST846, ST2399, and ST2400 were detected for K. pneumoniae; as well as E. cloacae ST182 and E. coli ST10. The fimA and uge genes were more likely to be identified in K. pneumoniae carbapenem-susceptible isolates (p = <0.001) and biofilm production was more liable to be observed in carbapenem-resistant isolates (p = <0.05). Conclusions Four Enterobacteriaceae species harboring the blaNDM-1 gene were detected in a nosocomial outbreak in Mexico; horizontal transfer and strain transmission were demonstrated for the blaNDM-1 gene. Given the variation in the size of the plasmid harboring blaNDM-1, complex rearrangements must also be occurring.